2019
DOI: 10.1016/j.jclepro.2018.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Detailed characterization of particle size fractions of municipal solid waste incineration bottom ash

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 44 publications
(48 reference statements)
6
41
2
Order By: Relevance
“…This was systematically verified in a recent investigation that sorted the BA in a range of different grain sizes. BA sorting produces new waste with the further disadvantage that smaller sized grains provide a larger reaction surface and, possibly, higher leaching of heavy metals already present at significant concentrations [14,15,[23][24][25]. Recovery of the smaller fraction of the BA was proposed in regard to pyroxene glass ceramics by heating at a high temperature [26].…”
Section: Introductionmentioning
confidence: 99%
“…This was systematically verified in a recent investigation that sorted the BA in a range of different grain sizes. BA sorting produces new waste with the further disadvantage that smaller sized grains provide a larger reaction surface and, possibly, higher leaching of heavy metals already present at significant concentrations [14,15,[23][24][25]. Recovery of the smaller fraction of the BA was proposed in regard to pyroxene glass ceramics by heating at a high temperature [26].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies were conducted on the physicochemical and engineering properties of MSWI-BA. It is concluded that MSWI-BAA made by fresh MSWI-BA after being pretreated, has a good particle size distribution and similar properties to natural aggregate and is suitable to be used in asphalt mixtures and cement concrete [4,5,9,13,14,19,20]. Some studies have consequently used MSWI-BAA to partially replace natural aggregate in asphalt mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Just as for Al, it is expected that some valuable metals also remain in BA, and that many of these come from incinerated WEEE (del Valle-Zermeño et al, 2017b). Nevertheless, given the highly heterogeneous distribution of the materials in BA (Loginova et al, 2019), the contents of one specific metal may differ as a function of particle size. Therefore, depending on their nature and composition, the metals contained in certain size fractions potentially has recycling value.…”
Section: Introductionmentioning
confidence: 99%